2019
DOI: 10.1101/519108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repertoire-Based Diagnostics Using Statistical Biophysics

Abstract: 9A fundamental challenge in immunology is diagnostic classification based on repertoire se-10 quence. We used the principle of maximum entropy (MaxEnt) to build compact representations 11 of antibody (IgH) and T-cell receptor (TCRβ) CDR3 repertoires based on the statistical biophysi-12 cal patterns latent in the frequency and ordering of repertoires' constituent amino acids. This 13 approach results in substantial advantages in quality, dimensionality, and training speed com-14 pared to MaxEnt models based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…These further investigations will elucidate the question of whether paratope sequence motifs may be used as in silico scanning devices for epitope-specific sequence regions in high-throughput antibody repertoire data for at least a subset of medically important antigens. Understanding the diversity and structure of antibody specificity on the repertoire level is also of importance for enhancing the precision of immune receptor-based immunodiagnostics where one of the most pressing current problems is a low signal-to-noise ratio (few antigen-specific sequences within a large pool of unrelated sequences) (Arora et al, 2019;Brown et al, 2019;Emerson et al, 2017;Ostmeyer et al, 2019).…”
Section: Epitope-specific Recognition Is Not Unilaterally Encoded Intmentioning
confidence: 99%
See 1 more Smart Citation
“…These further investigations will elucidate the question of whether paratope sequence motifs may be used as in silico scanning devices for epitope-specific sequence regions in high-throughput antibody repertoire data for at least a subset of medically important antigens. Understanding the diversity and structure of antibody specificity on the repertoire level is also of importance for enhancing the precision of immune receptor-based immunodiagnostics where one of the most pressing current problems is a low signal-to-noise ratio (few antigen-specific sequences within a large pool of unrelated sequences) (Arora et al, 2019;Brown et al, 2019;Emerson et al, 2017;Ostmeyer et al, 2019).…”
Section: Epitope-specific Recognition Is Not Unilaterally Encoded Intmentioning
confidence: 99%
“…Adaptive immune receptor repertoires represent a major target area for the application of machine learning in the hope that it may fast-track the in silico discovery and development of immunereceptor based immunotherapies and immunodiagnostics (Brown et al, 2019;Greiff et al, 2012;Mason et al, 2018Mason et al, , 2019Miho et al, 2018). The complexity of sequence dependencies that determine antigen binding (Dash et al, 2017;Glanville et al, 2017), immune receptor publicity (Greiff et al, 2017b) and immune status (immunodiagnostics) (Ostmeyer et al, 2019;Thomas et al, 2014) represent a perfect application ground for machine learning analysis (Arora et al, 2019;Cinelli et al, 2017;Greiff et al, 2017b;Liu et al, 2019;Mason et al, 2019;Sidhom et al, 2018;Sun et al, 2017). As discussed extensively in a recent literature review by us (Brown et al, 2019) the development of ML approaches for immune receptor datasets was and is still hampered by the lack of ground truth datasets.…”
Section: Interaction Sequence Motifs Provide Ground Truth For Benchmamentioning
confidence: 99%
“…Since the immune system is a dynamic reflection of the overall health of the organism, some antigen-specific signatures in the repertoire could be indicative of particular diseases [ 219 ]. It was demonstrated that statistical classifiers can identify immune profiles of patients with chronic lymphocytic leukemia [ 220 ], multiple sclerosis [ 221 ] or influenza [ 222 ] from NGS data alone. Further development of a larger variety of such models could result in versatile diagnostic tools for multiple conditions on the basis of an individual’s sequenced BCR repertoire [ 220 ].…”
Section: Developing Trendsmentioning
confidence: 99%
“…We validated that immuneSIM can generate immune repertoires that are similar to experimental repertoires (native-like) by evaluating a range of repertoire similarity measures. immuneSIM can also generate aberrant immune receptor repertoires to replicate a broad range of experimental, immunological or disease settings ( Arora et al , 2019 ; Brown et al , 2019 ) ( Supplementary Figs S2 – S7 ).…”
Section: Introductionmentioning
confidence: 99%